2019
DOI: 10.4085/1062-6050-81-18
|View full text |Cite
|
Sign up to set email alerts
|

Upper Extremity Musculoskeletal Characteristics and the Kerlan-Jobe Orthopaedic Clinic Questionnaire Score in Collegiate Baseball Athletes

Abstract: Context Upper extremity (UE) musculoskeletal injuries are common in baseball athletes due to the increased demand placed on the UE. The link between risk factors for UE musculoskeletal injuries and baseball athletes' perceived UE function and pain, as measured by the Kerlan-Jobe Orthopaedic Clinic (KJOC) questionnaire, is unclear. Objective To (1) describe the musculoskeletal characteristics of the UE (posture, range of motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…Two previous studies reported mean KJOC overall scores of 94.74 ± 6.79 for healthy uninjured college baseball players and 94.82 (95% CI 92.94-96.70) for professional pitchers. 11,14 The overall KJOC median scores reported in our sample were similar to the mean scores reported in these studies of healthy pitchers. Likewise, they did not identify significantly different KJOC scores between groups.…”
Section: Discussionsupporting
confidence: 87%
“…Two previous studies reported mean KJOC overall scores of 94.74 ± 6.79 for healthy uninjured college baseball players and 94.82 (95% CI 92.94-96.70) for professional pitchers. 11,14 The overall KJOC median scores reported in our sample were similar to the mean scores reported in these studies of healthy pitchers. Likewise, they did not identify significantly different KJOC scores between groups.…”
Section: Discussionsupporting
confidence: 87%
“…The 81.3 KJOC test score is highly accurate and reliable over other upper extremity questionnaire endpoints. A KJOC score of 81.3 or higher means that a player had resumed to playing with 95.1 % [20]. In this research, the KJOC score improved from 93.16 to 99.94 in Group A and from 93.18 to 99.42 in Group B.…”
Section: Closed Kinetic Chain Upper Extremity Stabilitymentioning
confidence: 50%
“…In our study, only pitchers with self-reported arm trouble during pitching were sampled. Previous studies reported that the KJOC scores of asymptomatic players were higher than 70 33 34 . In our current study, the KJOC score in the symptomatic group was 60.1±15.2, indicating mild dysfunction.…”
Section: Discussionmentioning
confidence: 77%